2019
DOI: 10.1039/c9sc00341j
|View full text |Cite
|
Sign up to set email alerts
|

Model peptide for anti-sigma factor domain HHCC zinc fingers: high reactivity toward 1O2 leads to domain unfolding

Abstract: The Zn(Cys)2(His)2 site of the anti-sigma factor ChrR reacts rapidly with 1O2 supporting its involvement in 1O2 sensing by this protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The amino acids sequence blast from NCBI does not show any known homology to other anti‐sigma factors, and the bioinformatics analyses do not show any conserved anti‐sigma factor domain neither. The first group of anti‐sigma factor contains an anti‐sigma domain, which features a conserved “H‐X 3 ‐C‐X 2 ‐C” zinc binding motif (Chabert et al., 2019). However, PG1659 does not exhibit any putative zinc‐binding motif and there is only one cysteine residue located in the transmembrane domain of PG1659.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The amino acids sequence blast from NCBI does not show any known homology to other anti‐sigma factors, and the bioinformatics analyses do not show any conserved anti‐sigma factor domain neither. The first group of anti‐sigma factor contains an anti‐sigma domain, which features a conserved “H‐X 3 ‐C‐X 2 ‐C” zinc binding motif (Chabert et al., 2019). However, PG1659 does not exhibit any putative zinc‐binding motif and there is only one cysteine residue located in the transmembrane domain of PG1659.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acids sequence blast from NCBI does not show any known homology to other anti-sigma factors, and the bioinformatics analyses do not show any conserved anti-sigma factor domain neither. The first group of anti-sigma factor contains an anti-sigma domain, which features a conserved "H-X 3 -C-X 2 -C" zinc binding motif (Chabert et al, 2019). However, PG1659 does not exhibit any puta- indicate that either another anti-sigma factor could be involved in regulation of PG0162, or the putative fused regulatory subdomain of PG0162 functions as an anti-sigma factor as reported (Sineva et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Even though in many oxidative stress sensing ZAS proteins, the dissociation between sigma and anti-sigma proteins takes place by the conformational change derived from the oxidative damage of the Zn 2+ ligands [ 15 ], it has been shown that singlet oxygen stimulates ChrR proteolysis [ 16 ]. However, it is unclear whether this turnover plays a key role in the release of RpoE or how this regulated proteolysis may occur [ 9 , 17 ].…”
Section: Ecf Sigma Factors With a Soluble Anti-sigma Factormentioning
confidence: 99%
“…Proteins that contain the [Zn(Cys) x (His) y ] architecture (where x+y=4) are implicated in HOCl sensing through a reversible oxidation process at the zinc‐bound cysteine(s), launching redox signaling cascades that can regulate protein activity, [4] mitigate protein aggregation, [5] increase bacterial resistance, [6] and alter bacterial localization [7] . While the reactivity of zinc‐bound thiolates to oxidants such as H 2 O 2 is well documented via experimental [8,9] and theoretical studies, [10,11] comparable work with HOCl is still in its infancy [12] . Furthermore, apart from modulating the protonation state [13] and nucleophilicity [14] of the bound thiolate at physiological pH, no additional role of Zn 2+ complexes in governing the reactivity of the bound thiolates toward oxidants has been explored.…”
Section: Figurementioning
confidence: 99%